Value Relevance of Corporate Governance Disclosure in Annual Reports: Evidence from Listed Banks in Kenya - Gitahi J (European Scientific Journal, ESJ, 2019)
This study investigates the value-relevance corporate governance disclosures published in the narrative part of annual reports of ten banks listed at the Nairobi Securities Exchange (NSE) over the entire period from year 2010 to year 2015. This work extends the line of research on value relevance by quantifying narrative accounting, in this case corporate governance disclosures using content analysis. In addition, in line with prior studies, this study employs the Ohlson´s (1995) value-relevance model and finds that corporate governance disclosure is significantly positively related to market value, measured by the average market price per share. The findings reveal that corporate governance disclosures influence investors’ perceptions and are therefore, vital to be included in annual reports, which are a major communication tool.